Testimony and secrecy of a traumatic past: the 'times of danger' in Sarhua's visual art. - González, Olga (2015)
This article discusses the fate of dangerous memories of war associated with the “internal armed conflict” in Peru. It focuses on the Andean community of Sarhua in Ayacucho and their experiences with political violence as depicted in a collection of paintings, Piraq Causa (Who Is Still to Blame?). A close examination of this visual testimonio reveals that some dangerous memories have been denied representation. I suggest that these become silences and absences that give expression to a “traumatic gap”, which includes memories of fratricidal violence and the community’s initial endorsement of the Maoist Shining Path. I argue that Piraq Causa reflects the magnified secrecy around events that the community agreed to deliberately “remember to forget”. In so doing, I also propose that the perceived gaps in the pictorial narrative provoke the unmasking of what is “secretly familiar” in Sarhua. To that extent, Piraq Causa exposes as much as it affirms the secrecy around traumatic memories of war.